The TGFβ-Induced Long Non-coding RNA TBULC Promotes the Invasion and Migration of Non-small Cell Lung Cancer Cells and Indicates Poor Prognosis - Zheng, Sufei; Lu, Zhiliang; Liu, Chengming; Wang, Xinfeng; Jin, Runsen; Mao, Shuangshuang; Huang, Jianbing; Lei, Yuanyuan; Zhang, Chaoqi; Sun, Nan; He, Jie (Frontiers in Oncology, 2019)
Objective: To investigate the biological function and clinicopathological significance of the TGFβ-induced long non-coding RNA (lncRNA) TBULC in non-small cell lung cancer (NSCLC) and to analyze its potential value in clinical diagnosis and treatment. Methods: RT-qPCR was used to detect the expression level of TBULC in NSCLC cells and tissues, and the correlation between the TBULC expression level and clinicopathological characteristics was analyzed. A cytoplasmic/nuclear fractionation assay was performed to define the cellular localization of the TBULC. A rapid amplification of cDNA ends (RACE) assay was performed to acquire the full-length sequence of the TBULC. Stable TBULC overexpression and TBULC knockdown cell clones were constructed by lentiviral infection, and Transwell assays were used to explore the effect of the TBULC on cell invasion and migration. Results: Stimulation with TGFβ in NSCLC cell lines significantly upregulated the expression level of the nuclear-localized lncRNA TBULC. The RACE assay indicated that the full-length TBULC sequence was 1,020 nucleotides, and the sequence was located on chromosome 15. Cell function experiments showed that the TBULC played a crucial role in promoting NSCLC metastasis. Knockdown of TBULC significantly suppressed the invasion and migration of NSCLC cells, and overexpression of TBULC had the opposite effects. The expression level of TBULC in 106 NSCLC tumor tissues was significantly higher than that in adjacent normal tissues, and TBULC was proven to be an independent prognostic factor in NSCLC patients [p = 0.030, OR = 0.513 (0.281–0.936)]. Conclusion: The TGFβ-induced lncRNA TBULC was upregulated in NSCLC and promoted the invasion and migration of NSCLC cells. TBULC was an independent prognostic factor and might be a potential biomarker for predicting the prognosis of NSCLC patients.